WORKPLACE EXERCISE PROGRAM TO REDUCE MUSCULOSKELETAL COMPLAINTS AND INCREASE THE PRODUCTIVITY OF BATIK MAKERS IN PEKALONGAN REGENCY - Irma Nahdliyyah, Ade; Hermawan, Agung; Putri, Anggrainy; Ario Fajar, Dwi; Akkapin, Supaphorn (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2024)
Pekalongan City is famous as the world's batik city which is a world heritage site determined by UNESCO (United Nations Educational, Scientific and Cultural Organization) on October 2, 2009. The development of the industry in both Pekalongan City and regency encompasses not only large-scale operations but also small and medium-sized enterprises. This is influenced by the increasing demand for batik both nationally and internationally. The impact of this increase causes an increase in workload and health problems. One of the problems that arise in batik workers is musculoskeletal complaints and increased physiological loads so that it can reduce worker productivity. Promotive and preventive measures can be implemented through workplace training programs. The training program provided to minimize these problems is by doing stretching and breathing exercises during their break times. By paying attention to the health of batik makers, it can maintain the sustainability of the batik industry in Pekalongan City. This study aims to help reduce musculoskeletal complaints of batik makers and increase their productivity by offering breathing exercises and active stretching exercises. This research is experimental research, using the same subject design (treatment by subject design). The number of research subjects 24 people. Based on the results of hypothesis testing, the average musculoskeletal complaint was significantly different between periods 1 and 2 with t=18.574and p value 0.000 (p<0.05). The average increase in productivity with a work pulse obtained t value = 4.956 and p value 0.000 (p <0.05). The results showed a significant decrease in musculoskeletal complaints and batik worker productivity in period 1 and period 2. Active stretching and breathing exercises for batik workers are urgently needed to reduce musculoskeletal complaints and a decrease in work pulse, which means it can reduce the physiological workload of batik workers so that it affects the health status of batik workers which in turn increases the productivity of batik workers.